Diameter Variability of Rotary Files and Their Corresponding Gutta-Percha Cones Using Laser Scan Micrometre - Mirmohammadi, Hesam; Sitarz, Monika; Shemesh, Hagay (Iranian Endodontic Journal, 2018)
Introduction: Manufacturers offer gutta-percha (GP) cones matched with different sizes of endodontic files as an attempt to simplify the obturation process and create a tight seal in the canal. The purpose of this study was to evaluate whether intra-manufacture GP diameters matched the diameters of their corresponding files at different levels using laser micrometre. Methods and Materials: Twenty files and corresponding GP master cones of Reciproc R40 (40/0.06) (VDW, Munich, Germany), WaveOne Large (40/0.08) (Dentsply Maillefer, Ballaigues, Switzerland), ProTaper F3 (30/0.09) (Dentsply Maillefer, Ballaigues, Switzerland), and Mtwo 40/0.06 (VDW, Munich, Germany) were examined using laser micrometre (LSM 6000 by Mitutoyo, Japan) with accuracy of 1 nm to establish their actual diameter at D0, D1, D3 and D6. The data was analysed using the independent t-test. The differences were considered at 0.05. Results: The diameter of GP master cones was significantly larger than that of the corresponding files at all levels in all brands. ProTaper GP diameter was closest to the file diameter at D1 (GP=0.35, File=0.35 mm), and D3 (GP=0.48, File=0.49). Conclusion: Within the same manufacturer, GP cone diameters do not match the diameters of their corresponding files. Clinicians are advised to use a GP gauge to cut the tip so as to appropriate the diameter from a smaller sized GP cone. Keywords: Diameter; Gutta-Percha; Root Canal; Rotary File; Size